Effects of Stereotactic Body Radiation Therapy Plus PD-1 Inhibitors for Patients With Transarterial Chemoembolization Refractory - Xiang, Yan-Jun; Wang, Kang; Zheng, Yi-Tao; Feng, Shuang; Yu, Hong-Ming; Li, Xiao-Wei; Cheng, Xi; Cheng, Yu-Qiang; Feng, Jin-Kai; Zhou, Li-Ping; Meng, Yan; Zhai, Jian; et al. (Frontiers in Oncology, 2022)
Background and Aims Patients with intermediate-stage hepatocellular carcinoma (HCC) who are refractory to transarterial chemoembolization (TACE) have a poor prognosis. This study aimed to explore whether stereotactic body radiation therapy (SBRT) combined with PD-1 inhibitors could improve the clinical outcomes of such patients. Methods This retrospective cohort study included patients with intermediate-stage HCC who were diagnosed with TACE refractoriness between January 2019 and December 2020 in the Eastern Hepatobiliary Surgery Hospital and the First Affiliated Hospital of Wenzhou Medical University. The patients were divided into two groups: (1) those who switched from TACE to receive stereotactic body radiotherapy (SBRT) combined with PD-1 inhibitors; (2) those who continued TACE treatment and added PD-1 inhibitors. Progression-free survival (PFS), overall survival (OS), and tumour response were assessed in both groups after becoming refractory to TACE treatment. Results Of the seventy-six patients included in this study, the median PFS was 19.6 months in the SBRT-IO group (n=31) and 10.1 months in the TACE-IO group (n=45, p<0.05). The SBRT-IO group also had a significantly higher OS than the TACE-IO group (p<0.05). The objective response rate (ORR) and disease control rate (DCR) were also better in the SBRT-IO group (ORR, 71.0% vs. 15.6%, OR=8.483, 95% CI 3.319-21.680, P < 0.001; DCR, 80.6% vs. 31.1%, OR=9.226, 95% CI 3.096-27.493, P < 0.001). Conclusions SBRT combined with a PD-1 inhibitor improves PFS and OS in TACE-refractory patients with intermediate-stage HCC. Therefore, this therapy is a suitable option in cases of TACE treatment failure.